Experimental analysis of four parallel single-phase natural circulation loops with small inner diameter. (5th November 2020) - Misale, Mario; Bocanegra, Johan Augusto; Borelli, Davide; Marchitto, Annalisa
Highlights: Heating power, inner tube diameter and heat sink temperature influence NCL behavior. Increasing the heat sink temperature the thermal performance of the NCL increase. Parallel connection of NCLs show a slight influence among the thermal performance. Abstract: In this paper, results from a new experimental setup consisting of four rectangular natural circulation loops are presented. The loops are vertically oriented, parallel and connected at the bottom; each one has an independent heat source of variable power and a common heat sink, and are studied under different configurations with varying parameters. The loops are symmetrical with 7 mm inner diameter, using distilled water as the working fluid transporting heat from the source to the heat sink by means of natural circulation. The experimental data are compared with the Vijayan's correlation showing a good agreement.